A Study On The Role Of Risk Management In Mitigating Financial Crisis (Journal of Informatics Education and Research, 2025)
This study examines how risk management influences the mitigation of financial crises, with a focus on the 2008 Global Financial Crisis and the COVID-19 pandemic. The 2008 crisis stemmed from excessive risk-taking, poorly understood financial instruments, and regulatory failures, whereas COVID-19 posed an external, non-financial shock that tested global economic resilience. Reforms such as Basel III improved financial stability, while the pandemic underscored the necessity of operational adaptability and digital transformation. The study emphasizes scenario planning, proactive governance, and diversified strategies as crucial tools for managing systemic shocks. Continued evolution of risk frameworks is essential as risks become increasingly complex and interconnected.